Pengaruh Penghindaran Pajak dan Struktur Modal terhadap Nilai Perusahaan dengan Tata Kelola Perusahaan sebagai Variabel Moderasi: Studi Empiris pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2024 - Mustika Randhy Saputri; Halkadri Fitra (Jurnal Eksplorasi Akuntansi, 2026)
This study examines the effect of corporate tax avoidance and capital structure on corporate value, with corporate governance serving as a moderating variable, in energy companies listed on the Indonesia Stock Exchange (IDX). All companies in the energy industry that are listed on IDX are part of research population. Using purposive sampling, 19 companies were selected based on their consistent publication of annual reports and absence of financial losses during the 2019–2024 period, resulting in 92 observations. IBM SPSS Statistics 27’s moderation regression analysis was used to examine the data. According to the results, corporate tax avoidance has no significant impact, while capital structure has a significant negative effect on corporate value. Furthermore, the relationship between corporate tax avoidance and corporate value is not moderated by corporate governance, but it does moderate the relationship between capital structure and corporate value. This study adds to the literature of empirical research already available on the factors that influence business value in developing nations, specifically in the energy industry of Indonesia. Practically, the findings provide guidance for corporate managers and policymakers in the energy sector to maintain an optimal debt to asset ratio, strengthen board independence, and ensure transparency in tax management. These measures are crucial for sustaining firm value, enhancing investor confidence, and promoting responsible financial governance in Indonesia’s energy industry.